The Impact of Moral Education Interventions on Adolescents' Sociomoral Reasoning Skills - Bulut, Sefa; Uka, Fitim; Rostami, Mehdi; Boltivets, Sergii (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to investigate the effectiveness of a moral training workshop designed to enhance sociomoral reasoning among adolescents. Drawing on the principles of ethical decision-making and moral development theory, the intervention sought to provide participants with the skills and knowledge necessary to navigate complex moral dilemmas. Employing a randomized controlled trial design, the study included 50 adolescents aged 12 to 16 years, randomly assigned to either the intervention or control group. The intervention comprised eight 75-minute sessions conducted over four weeks, focusing on moral dilemmas, perspective-taking, ethical decision-making, and reflection on personal values. Sociomoral reasoning was assessed using the Defining Issues Test-2 (DIT-2) at three time points: pre-intervention, post-intervention, and a two-month follow-up. Analysis of Variance with Repeated Measurements indicated significant improvements in sociomoral reasoning scores for the experimental group compared to the control group (p < 0.01). The experimental group showed a notable increase in DIT-2 scores from pre-test to post-test, which was maintained at the two-month follow-up. The Bonferroni Post-Hoc Test further confirmed these findings, highlighting significant advancements in sociomoral reasoning immediately following the workshop, with sustained effects over time. The moral training workshop effectively enhanced sociomoral reasoning among adolescents, suggesting that structured moral education interventions can significantly impact ethical development. These findings underscore the importance of incorporating moral reasoning training in adolescent education, providing a foundation for ethical decision-making that can guide behavior across various life contexts.